2016
DOI: 10.5306/wjco.v7.i2.135
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Enhancer of Zeste Homolog 2 as a promising strategy for cancer treatment

Abstract: Polycomb group proteins represent a global silencing system involved in development regulation. In specific, they regulate the transition from proliferation to differentiation, contributing to stem-cell maintenance and inhibiting an inappropriate activation of differentiation programs. Enhancer of Zeste Homolog 2 (EZH2) is the catalytic subunit of Polycomb repressive complex 2, which induces transcriptional inhibition through the tri-methylation of histone H3, an epigenetic change associated with gene silencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 138 publications
0
20
0
Order By: Relevance
“…It has been found that the over expression of EZH2 leads to a number of cancer with elevated levels of EZH2 found in breast as well as prostate cancer patients. The elevated level of EZH2 may be attributed to the mutation of residues Y641 to a phenylalanine (Y641F) and A677 to a glycine (A677G) present in the SET domain, which increases the activity of trimethylation in the protein 1 2 .…”
mentioning
confidence: 99%
“…It has been found that the over expression of EZH2 leads to a number of cancer with elevated levels of EZH2 found in breast as well as prostate cancer patients. The elevated level of EZH2 may be attributed to the mutation of residues Y641 to a phenylalanine (Y641F) and A677 to a glycine (A677G) present in the SET domain, which increases the activity of trimethylation in the protein 1 2 .…”
mentioning
confidence: 99%
“…Overexpression of EZH2 has been found to be associated with tumor aggressiveness, metastasis, and poor prognosis in multiple cancers [17-20], including lung cancer [21, 22]. MiR-26a was documented to suppress tumor growth by targeting EZH2 in some tumors [23-25].…”
Section: Resultsmentioning
confidence: 99%
“…RT is used as an adjuvant or neoadjuvant treatment in MPM, mainly in a palliative setting (8)(9)(10). As standard practice, patients undergoing an EPP receive adjuvant conventionally fractionated RT (50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60) in the ipsilateral hemithorax area (18,19). In node-negative MPM patients, neoadjuvant therapy, based on intensity-modulated RT (IMRT) consisting of a fractionated irradiation of 5-6 Gy, is delivered before EPP (20)(21)(22).…”
Section: Radiotherapymentioning
confidence: 99%